2021
DOI: 10.51791/njap.v30i1.1429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microdesmis puberula leaf meal as feed ingredient in broiler starter diets

Abstract: A 21-day feeding trial was conducted to evaluate the leaf meal of Microdesmis puberula as feed ingredient in broiler starter diets. Microdesmis puberula is a preferred tropical browse plant. The leaves were harvested, chopped to facilitate drying, spread evenly in a room for four days until the material becomes crispy while still retaining it's greenish colouration. The material was milled using a hammer mill to produce the leaf meal. Microdesmis puberula leaf meal contain 17.32% crude protein, 6.52% ether ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Wang et al (2021) also receded no effect of the prime and California types of hulls in different levels on egg weight, yolk and albumen weight, egg specific gravity, haugh unit, shell weight, and shell thickness in laying hens. The values recorded for internal characteristics of the egg were in line with the report for normal fresh eggs (Emenalom, 2001;Esonu et al, 2004;Dongmo and Fomunyam, 2005). Total revenue, profit, and cost-benefit ratio during different phases were recorded higher for the control group which is due to higher egg production as compared to the soy hull containing different groups.…”
Section: Discussionsupporting
confidence: 85%
“…Wang et al (2021) also receded no effect of the prime and California types of hulls in different levels on egg weight, yolk and albumen weight, egg specific gravity, haugh unit, shell weight, and shell thickness in laying hens. The values recorded for internal characteristics of the egg were in line with the report for normal fresh eggs (Emenalom, 2001;Esonu et al, 2004;Dongmo and Fomunyam, 2005). Total revenue, profit, and cost-benefit ratio during different phases were recorded higher for the control group which is due to higher egg production as compared to the soy hull containing different groups.…”
Section: Discussionsupporting
confidence: 85%
“…According to Butcher et al (1983), external and internal offal percentages tend to increase as slaughter weight of the animal increase. Esonu et al (2008) reported that organ weights are an index of nutrients retained by the birds.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson and Sheldon (2004) also reported that poor nutrition affects snail growth and causes a drop in the reproductive performance, this is evident in the result of laying snails fed roughage/natural plant material (UPWP) which had the least reproductive performance as compared to concentrate GNCD-LLLM fed snails. According to Amaefule and Onwudike (2000), Ani and Okeke (2003), Esonu et al (2003), Oyeagu et al (2015) and Oyeagu et al (2018), the most important factor influencing the performance of animals under captivity is the quality of diet offered to the animals. This study corroborates the claim of Nyameasem and Borketey-La (2014) that layer mash (a concentrate ration) supported reproduction in the snails better than Pawpaw fruit diet which gave the poorest result.…”
Section: Discussionmentioning
confidence: 99%